Real‐World Effectiveness of Switching to Oral or Infusion Versus Injectable Disease‐Modifying Therapy in Pediatric Multiple Sclerosis - Abrams, Aaron W.; Waltz, Michael; Casper, T. Charles; Aaen, Gregory; Benson, Leslie A.; Bernfeld, Eva‐Chava M.; Charvet, Leigh E.; Chitnis, Tanuja; Francisco, Carla; Gorman, Mark P.; Graves, Jennifer S.; Krupp, Lauren; et al. (Annals of neurology, 2025)
To assess real-world effectiveness of switching disease-modifying therapy (DMT) in pediatric multiple sclerosis (MS) and clinically isolated syndrome (CIS) initially treated with platform injectables on disease activity. Of 2615 pediatric-onset demyelinating disease patients at 12 clinics in the United States (US) Network of Pediatric MS Centers, those with MS/CIS on initial therapy with a platform injectable who switched to another class of platform injectable, oral or infusion DMT were analyzed. Relapse rate was modeled with negative binomial regression, adjusted for preidentified confounders. A total of 212 children switched DMT before age 18 (67% female, 95% MS). Ninety-three switched from injectable to injectable, 76 injectable to oral, and 43 injectable to infusion. Switchers to oral or infusion were older at onset (injectable 12.3 years, oral 13.5 years, and infusion 14.2 years) and switch (injectable 14.6 years, oral 16.0 years, and infusion 15.7 years). Switchers to infusion DMT were more likely to have enhancing lesions (injectable 45%, oral 28%, and infusion 67%). Compared to injectable (annualized relapse rate [ARR] = 0.88, 95% confidence interval [CI] = 0.52-1.48), relapse rates were lower for injectable to oral (ARR = 0.34, 95% CI = 0.20-0.57; rate ratio: 0.38, 95% CI = 0.21-0.69) and injectable to infusion (ARR = 0.18, 95% CI = 0.09-0.37; rate ratio: 0.21, 95% CI = 0.10-0.44) (p < 0.001). Adjusted number needed to treat in person-years to prevent 1 relapse with oral over injectable was 1.84 (95% CI = 1.03-8.69) and infusion over injectable 1.43 (95% CI = 1.00-3.88). Switching from platform injectable to oral or infusion compared to other platform injectable DMT led to better disease control in pediatric MS. Long-term safety data are required. ANN NEUROL 2025.